MORB-DERIVED VARISCAN AMPHIBOLITES IN THE NORTHERN APENNINE BASEMENT: THE CERRETO METAMORPHIC SLICES (TUSCAN-EMILIAN APENNINE, NW ITALY) - Molli, Giancarlo; Montanini, Alessandra; Frank, Wolfgang (Ofioliti, 2002)
In the Cerreto area metamorphic rocks belonging to the basement of the Northern Apennine are exposed in association with Triassic evaporites and quartzites. The Cerreto basement rocks consist of lenses and plurimetric bodies of amphibolites included in a sequence of metapsammites (biotite and/or muscovite schists).Both metasediments and amphibolites underwent a retrograde evolution starting from an initial medium-pressure amphibolite stage (M1: P ~ 8 kbar, T ~ 650°C) down to greenschist condition. The amphibolites show a well preserved earlier foliation associated with development of green amphibole (aluminotschermakite) + plagioclase + quartz + ilmenite assemblage followed by partial retrograde recrystallization in epidote-amphibolite facies under static conditions and along shear zones (M2: ~ P 4-5 kbar, T ~ 530°C); pre-kinematic garnet porphyroblasts rimmed by amphibole + plagioclase coronas are widespread. Metasediments show a pervasive mylonitic deformation associated with amphibolite to greenschist facies assemblages and rare relics of an earlier fabric, testified by inclusions of quartz + biotite in plagioclase and garnet porphyroclasts. The latest stages of deformation are accompanied in both metasediments and amphibolites by retrograde development of greenschist-facies assemblages in millimeter-scale shear zones crosscutting the former structures.Major and trace element compositions of the amphibolites suggest that most protoliths are cogenetic and could be related through fractional crystallization of plagioclase + olivine and/or pyroxene from variably evolved tholeiitic liquids. Geochemical data also indicate that most of the amphibolites have protolith features resembling Enriched-type MORB.40Ar/39Ar dating performed on two hornblende samples (312 and 328 Ma) indicate a Variscan age for the amphibolite-facies metamorphism implying that the Cerreto metamorphic rocks belong to a unit deformed and metamorphosed at deep structural levels during the main deformational event (i.e. collisional stage) of the Southern Europe Variscan belt. The present tectonic setting of the Cerreto rocks, i.e. rootless slices within cover unit, could be related to the Apenninic thrusting. The Apenninic tectonic history likely occurred at very high structural levels without development of pervasive syn-metamorphic structures.